Morphine as first medication for treatment of cancer pain - Nunes, Beatriz C. (2014)
BACKGROUND AND OBJECTIVES:the medications used according to the recommendation of the World Health Organization do not promote pain relief in a number of patients with cancer pain. The aim of this study was to evaluate the use of morphine as first medication for the treatment of moderate cancer pain in patients with advanced and/or metastatic disease, as an option to the recommendations of the World Health Organization analgesic ladder.METHOD:sixty patients without opioid therapy, with >18 years of age, were randomized into two groups. G1 patients received medication according to the analgesic ladder and started treatment with non-opioids in the first, weak opioids in the second, and strong opioids in the third step; G2 patients received morphine as first analgesic medication. The efficacy and tolerability of initial use of morphine were evaluated every two weeks for three months.RESULTS:the groups were similar with respect to demographic data. There was no significant difference between the groups regarding pain intensity, quality of life, physical capacity, satisfaction with treatment, need for complementation and dose of morphine. In G1 there was a higher incidence of nausea (p = 0.0088), drowsiness (p = 0.0005), constipation (p = 0.0071) and dizziness (p = 0.0376) in the second visit and drowsiness (p = 0.05) in the third.CONCLUSIONS:the use of morphine as first medication for pain treatment did not promote better analgesic effect than the ladder recommended by World Health Organization, with higher incidence of adverse effects.